Harlequin Syndrome with Crossed Sympathetic Deficit of the Face and Arm - Moon, So Young (The Korean Academy of Medical Sciences, 2005)
Harlequin syndrome is characterized by unilateral hyperhidrosis and flushing, which are predominantly induced by heat or exercise. Usually, the sympathetic deficits confine to the face. Rarely, the autonomic deficits involve the arm or the parasympathetic neurons in the ciliary ganglia. We report a 43-yr-old woman who presented with facial flushing and sweating in the right side, which were mainly induced by exercise. The facial flushing accompanied relative coldness in the right arm. Valsalva maneuver, cold pressure and 0.125% pilocarpine test, and computed tomography of the chest were normal. The crossed sympathetic deficit in the left face and right arm suggested that the lesions were multifocal. The sympathetic impairment in our patient may lie on a spectrum of pre- and postganglionic autonomic dysfunction, which was observed in Holmes-Adie, Ross, and Guillain-Barré syndrome.